Cardiac dose-sparing effects of deep-inspiration breath-hold in left breast irradiation : Is IMRT more beneficial than VMAT? - Sakka, Mazen; Kunzelmann, Leonie; Metzger, Martin; Grabenbauer, Gerhard (Strahlentherapie und Onkologie, 2017)
BACKGROUND: Given the reduction in death from breast cancer, as well as improvements in overall survival, adjuvant radiotherapy is considered the standard treatment for breast cancer. However, left-sided breast irradiation was associated with an increased rate of fatal cardiovascular events due to incidental irradiation of the heart. Recently, considerable efforts have been made to minimize cardiac toxicity of left-sided breast irradiation by new treatment methods such as deep-inspiration breath-hold (DIBH) and new radiation techniques, particularly intensity modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT). The primary aim of this study was to evaluate the effect of DIBH irradiation on cardiac dose compared with free-breathing (FB) irradiation, while the secondary objective was to compare the advantages of IMRT versus VMAT plans in both the FB and the DIBH position for left-sided breast cancer. METHODS: In all, 25 consecutive left-sided breast cancer patients underwent CT simulation in the FB and DIBH position. Five patients were excluded with no cardiac displacement following DIBH-CT simulation. The other 20 patients were irradiated in the DIBH position using respiratory gating. Four different treatment plans were generated for each patient, an IMRT and a VMAT plan in the DIBH and in the FB position, respectively. The following parameters were used for plan comparison: dose to the heart, left anterior descending coronary artery (mean dose, maximum dose, D25% and D45%), ipsilateral, contralateral lung (mean dose, D20%, D30%) and contralateral breast (mean dose). The percentage in dose reduction for organs at risk achieved by DIBH for both IMRT and VMAT plans was calculated and compared for each patient by each treatment plan. RESULTS: DIBH irradiation significantly reduced mean dose to the heart and left anterior descending coronary artery (LADCA) using both IMRT (heart -20%; p = 0.0002, LADCA -9%; p = 0.001) and VMAT (heart -23%; p = 0.00003, LADCA -16%; p = 0.01) techniques as compared with FB radiation. There were no significant changes in left lung dose by IMRT; however, with VMAT planning, mean dose to the left lung was reduced by -4% (p = 0.0004). In addition, DIBH significantly increased the mean dose to the contralateral breast with IMRT (+14%, p = 0.002) and significantly reduced the dose to the contralateral breast with VMAT planning (-9%, p = 0.003) compared with the FB position. Additionally, in comparison with VMAT, the IMRT technique reduced mean heart dose both in the FB and the DIBH-position by -30% (p = 0.0004) and -26% (p = 0.002), respectively. Furthermore, IMRT increased the mean dose to the left lung in both the FB and the DIBH position (+5%, p = 0.003, p = 0.006), respectively. There were no significant changes in dose to the right lung and contralateral breast either in the FB or DIBH position between IMRT and VMAT techniques. CONCLUSION: Left-sided breast irradiation is best performed in the DIBH position, since a considerable dose sparing to the heart and LADCA can be achieved by using either IMRT or VMAT techniques. A significant additional decrease in heart and LADCA dose by IMRT in both FB and DIBH irradiation was seen compared with VMAT.
EVALuna2:36526